An Ultrastructural Study of the Extruded Polar Tube of Anncaliia algerae (Microsporidia). (8th August 2019) - Takvorian, Peter M.; Han, Bing; Cali, Ann; Rice, William J.; Gunther, Leslie; Macaluso, Frank; Weiss, Louis M.
Abstract: All microsporidia share a unique, extracellular spore stage, containing the infective sporoplasm and the apparatus for initiating infection. The polar filament/polar tube when exiting the spore transports the sporoplasm through it into a host cell. While universal, these structures and processes have been enigmatic. This study utilized several types of microscopy, describing and extending our understanding of these structures and their functions. Cryogenically preserved polar tubes vary in diameter from 155 to over 200 nm, noticeably larger than fixed‐sectioned or negatively stained samples. The polar tube surface is pleated and covered with fine fibrillar material that projects from the surface and is organized in clusters or tufts. These fibrils may be the sites of glycoproteins providing protection and aiding infectivity. The polar tube surface is ridged with 5–6 nm spacing between ridges, enabling the polar tube to rapidly increase its diameter to facilitate the passage of the various cargo including cylinders, sacs or vesicles filled with particulate material and the intact sporoplasm containing a diplokaryon. The lumen of the tube is lined with a membrane that facilitates this passage. Careful examination of the terminus of the tube indicates that it has a closed tip where the membranes for the terminal sac are located.